Construction of Supercapacitor‐Based Ionic Diodes with Adjustable Bias Directions by Using Poly(ionic liquid) Electrolytes. Issue 31 (24th June 2021) - Feng, Jianze; Wang, Yan; Xu, Yongtai; Ma, Hongyun; Wang, Gaowei; Ma, Pengjun; Tang, Yu; Yan, Xingbin
Abstract: The newly emerging supercapacitor‐diode (CAPode), integrating the characteristics of a diode into an electrical‐double‐layer capacitor, can be employed to extend conventional supercapacitors to new technological applications and may play a crucial role in grid stabilization, signal propagation, and logic operations. However, the reported CAPodes have only been able to realize charge storage in the positive‐bias direction. Here, bias‐direction‐adjustable CAPodes realized by using a polycation‐based ionic liquid (IL) or a polyanion‐based IL as electrolyte in an asymmetric carbon‐based supercapacitor architecture are proposed. The resulting CAPodes exhibit charge‐storage function at only the positive‐ or negative‐bias direction with a high rectification ratio (≈80% for rectification ratio II, RR II ) and an outstanding cycling life (4500 cycles), representing a crucial breakthrough for designing high‐performance capacitive ionic diodes. Abstract : An ion‐regulation strategy to design bias‐direction‐adjustable supercapacitor‐diodes is demonstrated. Such multifunctional devices show excellent charge‐storage performance and rectification performance, which fills a gap in the current capacitive ionic diodes.